Development Of A Green Economic Village Through The Eco-Enzyme Program In Candisari Village Lamongan, East Java: Pembangunan Desa Ekonomi Hijau Melalui Program EkoenzimDi Desa Candisari Lamongan Jawa Timur - Retnowati, Wiwin; Khaerunnisa, Siti Khaerunnisa; Fauzi, R. Moh. Qudsi; Maharani, Sekar (Universitas Lancang Kuning, 2024)
Organic waste is developed into ecoenzymes with science and technology through fermentation processes that produce environmentally friendly products and can reduce pollution. The activity partners are the women of PKK RT. 015/RW. 08 Candisari Village, Sambeng District, Lamongan Regency, with the priority of developing a green economic village through managing organic waste into eco-enzymes. The activities were followed by 34 PKK women participants with stages of presentation of eco-enzyme material, small-scale manufacturing process, mentoring, and evaluation. Based on the pre-test and post-test results showed an increase in the knowledge of ecoenzymes from 0% 0% to enough knowledge of 8.8% and knowledge of 91.2%. The ability to make eco-enzymes increased from 0% tto enough knowledge of 5.9% and knowledge of 94.1%. The indicators of increasing knowledge show that community service activities are successful.